Intellectual Capital Performance Level of Indonesian Financial Sector - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 10 No.1, 2011 JBE UNKLAB, 2011)
The growing importance of intangible assets in recent decades and the reliance on financial measures alone may mislead the business operations in the long-term have motivated this study.  Focusing on listed Indonesian financial sectors, this study aims to empirically find out if the five sub-sectors under study reveal similar or different level of Intellectual Capital Performance. This study also seeks to introduce the new indicator of intellectual capital performance, VAIC TM for business analysis.  The result of this study reveals that in 2007, the overall mean of VAIC TM among the group of banks was higher than the four non-bank financial institutions.